2015
DOI: 10.1080/11956860.2015.1047142
|View full text |Cite
|
Sign up to set email alerts
|

A forest health inventory assessment of red fir (Abies magnifica) in upper montane California

Abstract: We investigated the forest health of red fir (Abies magnifica) and how it compared with commonly-associated species Jeffrey pine (Pinus jeffreyi), lodgepole pine (Pinus contorta) and white fir (Abies concolor) in the upper montane forests of California. We evaluated tree mortality rates, changes in the density of recently-dead trees and the amount of insect and disease damage on live trees from comprehensive forest inventories. The annual mortality rate for red fir was 1.8%, while the rates for Jeffrey pine, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Death of the lower branches has been attributed to dwarf mistletoe infection alone, to infection of dwarf mistletoe-infected branches by a canker fungus (Cytospora abietis Saccardo) and/or to branch shading in dense, old-growth fir stands (Parmeter & Scharpf, 1989;Scharpf, 1969a;Scharpf & Bynum, 1975;Scharpf & Parmeter, 1976). Mortenson, Gray, and Shaw (2015) also observed high levels of branch dieback in RFDM-infected red firs and attributed the widespread branch mortality to Cytospora canker. Substantial death of fir dwarf mistletoe-infected branches infected with Cytospora canker resulting in reduced live crown ratios and tree vigour has also been reported for grand fir (Abies grandis [Douglas ex D. Don] Lindley) in Oregon (Filip, 1984).…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…Death of the lower branches has been attributed to dwarf mistletoe infection alone, to infection of dwarf mistletoe-infected branches by a canker fungus (Cytospora abietis Saccardo) and/or to branch shading in dense, old-growth fir stands (Parmeter & Scharpf, 1989;Scharpf, 1969a;Scharpf & Bynum, 1975;Scharpf & Parmeter, 1976). Mortenson, Gray, and Shaw (2015) also observed high levels of branch dieback in RFDM-infected red firs and attributed the widespread branch mortality to Cytospora canker. Substantial death of fir dwarf mistletoe-infected branches infected with Cytospora canker resulting in reduced live crown ratios and tree vigour has also been reported for grand fir (Abies grandis [Douglas ex D. Don] Lindley) in Oregon (Filip, 1984).…”
Section: Discussionmentioning
confidence: 87%
“…The percentage of dead true firs was low in plots (<4%), but was much higher in transects: 12% for red fir and 10% for white fir. Mortenson et al, (2015) reported annual mortality rates in the SNM for red fir and white fir of 1.8% and 3.0%, respectively. These annual mortality rates were based on data from permanent plots, not temporary plots.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations